Islamic Education Based on Multiculturalism in Post-Social Conflict Reconciliation - Markarma, Andi; Djubaedi, Dedi; AP, A. Nurfadhillah; Yusuf, Khaeruddin; S, Andi Bahri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The conceptualization of Islamic education based on multiculturalism is important to implement to resolve and reconcile peace after social conflict. For this reason, this research was carried out to identify and describe important concepts that are the basis of multicultural Islamic education in post-social conflict reconciliation. This research used a descriptive qualitative research paradigm with documentation and field research models in the community and Islamic educational institutions in Sigi Regency, Central Sulawesi. Data collection techniques use documentation, interviews, and observation. The reduced and classified data were then studied and conceptualized based on an in-depth study based on the theoretical perspective of Islamic education and multiculturalism. The results of the research are that the conceptualization of Islamic education based on multiculturalism in post-social conflict reconciliation is conceptualized in the form of (1) Islamic education to understand human differences; (2) Islamic education becomes a set of values ​​for social life; (3) Islamic education accommodates local values; and (4) Islamic education becomes the foundation for social reconciliation. This conceptualization confirms that Islamic education based on multiculturalism can be used as an alternative in post-social conflict reconciliation.